Synthesis of 2-Aryl-1-arylmethyl-1H-benzimidazoles Catalyzed by Brønsted Acidic Ionic Liquid under Ultrasonic Irradiation - Liu, Wei-Hua; Gao, Shu-Tao; Zhang, Peng-Hui; Zhou, Xin; Wang, Chun (Asian Journal of Chemistry, 2014)
A series of 2-aryl-1-arylmethyl-1H-benzimidazoles were synthesized through the condensation reactions of aromatic aldehydes and o-phenylenediamine using Brønsted acidic ionic liquid, 3-methyl-1-(3-sulfopropyl)-imidazolium trifluoro acetate, as catalyst under ultrasonic irradiation condition. The yields of the products were in the range from 85 % to 97 %. The Brønsted acidic ionic liquid can be recovered and reused at least five consecutive cycles without significant loss of its catalytic activity. The results indicated that the proposed method is easy, efficient and environmental friendly for the preparation of 2-aryl-1-arylmethyl-1H-benzimidazoles.